2023
DOI: 10.1177/15579883231165626
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Knowledge About Male Breast Cancer Among Patients at Tertiary Medical Center

Abstract: In the overall population, the incidence of breast cancer in men is lower than in women. Men’s breast cancer awareness is affected both by the low incidence of breast cancer in men and by the presence of a perception that breast cancer can only be seen in women in society. This study aims to determine this awareness and guide future studies on improving social awareness. This study examined male and female patients aged 18 to 75 years who were admitted to our hospital’s general surgery outpatient clinic. A que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Only 38.9% of the study participants knew that men can also develop BC. The study noted that women have a higher level of BC awareness than men [45]. An important role in the early detection of MBC is played by education campaigns and the introduction of breast screening programs, at least for men with a family history of BC.…”
Section: Discussionmentioning
confidence: 91%
“…Only 38.9% of the study participants knew that men can also develop BC. The study noted that women have a higher level of BC awareness than men [45]. An important role in the early detection of MBC is played by education campaigns and the introduction of breast screening programs, at least for men with a family history of BC.…”
Section: Discussionmentioning
confidence: 91%
“…This seems to be related to the lack of knowledge about this disease in the general population. One study including 411 patients performed by Altiner et al demonstrated that more than half of the participants (61.1%) were not aware of the possibility of this disease in men [ 41 ]. Raising awareness of this uncommon disease will enable men to be diagnosed earlier and possibly increase their survival time.…”
Section: Discussionmentioning
confidence: 99%
“…The latest research findings indicate that the relatively low social awareness of male BC may be a crucial contributing factor to the high mortality rate in males. Men often fail to receive timely detection and diagnosis during the early and less advanced stages of BC, thereby missing the opportunity for treatment to extend their lifespans 44 . This highlights the importance of not only focusing on female BC but also addressing the growing burden of male BC.…”
Section: Discussionmentioning
confidence: 99%